Implementasi Norma Internasional mengenai Kebebasan Beragama dan Berkeyakinan di Indonesia - Muhammad Iqbal Yunazwardi; Aulia Nabila (Universitas Diponegoro, 2021)
Indonesia has ratified the International Covenant of Civil and Political Rights (ICCPR) and guarantees freedom of religion or belief (FoR). However, violations of FoR in Indonesia remains occur after 2015. This paper analyses this issue using the concept of norms localization which assumes that the implementation of international norms is the main factor that affects Indonesia’s effort to implement the FoR. There is a gap between international norms, that is Article 18 of the ICCPR and the Indonesia’s positive law regulating FoR. In addition, the characteristics of religious demography and religious behaviour of Indonesian people affect the implementation of FoR. As a result, the implementation of the norms by local actors such as the National Commission of Human Rights (Komnas HAM) is diminished. This paper concludes that in implementing the norms the government interprets the social and political context at societal level. The government is oftently forced by certain groups so it could be the potential violator of the FoR regulations that has been agreed upon.